Compact Band-Pass and Band-Reject Microwave Filters Using Partial H-Plane Waveguide and Dielectric Layers - Ali Ghajar; Habib Ghorbaninejad Foumani (International Journal of Information and Communication Technology Research, 2014)
In this paper, microwave filters were designed using dielectric layers, which were transversely located inside a partial H-plane waveguide. The proposed structure can be used to design microwave filters with arbitrary frequency response including band-pass or band-reject filters. Its longitude was reduced by about 31% compared with conventional partial H-plane band-pass filters. Since the cross-section of partial H-plane waveguide, in a determined frequency range, is one quarter of the conventional waveguide, then the proposed filter has the cross-section of one quarter compared with the counterpart E-plane waveguide filter. Besides compactness, it is easy to fabricate, cheap, mass producible, mechanically stable, and capable of sustaining high microwave power and has very good adjustment to any arbitrary ideal filter. The proposed partial H-plane band-pass filter and its performance in terms of compactness and adjustment to any arbitrary ideal filter were verified by designing and simulating three filters.